A Systematic Scoping Review on Research Focusing on Professionals' Attitudes toward School Attendance Problems - Selina Eckhoff Hamadi; May Irene Furenes; Trude Havik (MDPI AG, 2024)
This systematic scoping review was conducted to determine the extent of existing research on professionals' attitudes toward school attendance problems (SAPs), including school refusal (SR), truancy (TR), school withdrawal (SW), and school exclusion (SE), in basic education. Five databases (ERIC, Academic Search Ultimate, Scopus, PsycINFO, and Web of Science) were systematically searched for relevant literature. Forty-five studies met the inclusion criteria that were set prior to the search and were eligible for inclusion. The results of this systematic scoping review reveal that there has been a continuous increase in studies addressing professionals' attitudes toward SAPs since 2000, with the greatest number of studies published after 2019 and in Europe. Most studies were descriptive, cross-sectional, and used a qualitative approach and the most common informants were school-based professionals (i.e., teachers, school administrators, and other school staff). The included studies used a variety of concepts referring to SAPs and types of SAPs, underlining the present challenges in terminology and definitions that characterize the research field. The results of this review contribute to identifying gaps in knowledge and offer guidelines for future research as a prerequisite to enhance the contemporary comprehension of SAPs in research and in practice.